Fluorogenic Probing of Specific Recognitions between Sugar Ligands and Glycoprotein Receptors on Cancer Cells by an Economic Graphene Nanocomposite - Zhang, Hai-Lin; Wei, Xiao-Li; Zang, Yi; Cao, Jia-Yi; Liu, Shanshan; He, Xiao-Peng; Chen, Qibin; Long, Yi-Tao; Li, Jia; Chen, Guo-Rong; Chen, Kaixian (Advanced materials (Weinheim), 2013)
Economical nanocomposites based on π‐stacking of N‐acetyl glycosyl rhodamine B to graphene oxide (GO) are simply prepared. These “sweet” GO‐materials are proven to be admirable for the fluorogenic recognition of specific intercellular sugar‐based ligand‐glycoprotein receptor interactions of interest.